Emerging Technologies in Women's Health Volume 1 : Robotic Surgery in Gynecology. - Tulandi, T. (Togas) (Bentham Science Publishers, 2011)
Emerging Technologies in Women's Health is the first of a series of books dedicated providing updates on rapid advances in new technologies in women's healthcare for researchers and clinicians. This e-book explains techniques of performing minimally invasive robotic surgery in a concise manner. Each chapter is contributed by experts in advanced laparoscopic and robotic surgery and contains several useful line drawn illustrations and photographs. This e-book should be of interest to gynecologic surgeons, fellows and residents.